1993
DOI: 10.1029/93tc01131
|View full text |Cite
|
Sign up to set email alerts
|

Structure and kinematics of Upper Cenozoic extensional detachment on Naxos and Paros (Cyclades Islands, Greece)

Abstract: This paper presents a study of the ductile and brittle deformation on Naxos and Paros islands (Cyclades, Greece). Previous maps and studies of the two islands have shown that a major low‐angle fault zone separates surface rocks above the contact from an initially deep‐seated unit below, showing a metamorphic evolution from high to low pressures. Structural analysis, as well as available stratigraphical, metamorphic, and geochronological data taken together demonstrate that this fault zone is a major normal‐sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
266
1
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 232 publications
(286 citation statements)
references
References 57 publications
(16 reference statements)
13
266
1
6
Order By: Relevance
“…Vertical axis block rotations in the west Aegean region (50°since ∼15 Ma [van Hinsbergen et al, 2005b]) are well established, but have been shown to postdate most of the back-arc extension history , illustrating that the block rotation history of the Aegean is perhaps partly accommodated by, but not directly caused (if at all) by, back-arc extension. Moreover, most of the rotating region lies to the northwest of the Cycladic and south Aegean crystalline complexes where much of the Aegean extension was accommodated [Gautier et al, 1993;Fassoulas et al, 1994;Gautier and Brun, 1994;Jolivet et al, 1994bJolivet et al, , 1996Ring et al, 2003b;Jolivet and Brun, 2010]. Although relations between rotation and exhumation in the Rhodope core complex have been postulated [Brun and Sokoutis, 2007;van Hinsbergen et al, 2008a], the region that could have experienced major extension-related rotations in the west lies offshore central or southwestern Greece (Figure 1).…”
Section: Hinsbergen Et Al: Exhumation With a Twistmentioning
confidence: 99%
“…Vertical axis block rotations in the west Aegean region (50°since ∼15 Ma [van Hinsbergen et al, 2005b]) are well established, but have been shown to postdate most of the back-arc extension history , illustrating that the block rotation history of the Aegean is perhaps partly accommodated by, but not directly caused (if at all) by, back-arc extension. Moreover, most of the rotating region lies to the northwest of the Cycladic and south Aegean crystalline complexes where much of the Aegean extension was accommodated [Gautier et al, 1993;Fassoulas et al, 1994;Gautier and Brun, 1994;Jolivet et al, 1994bJolivet et al, , 1996Ring et al, 2003b;Jolivet and Brun, 2010]. Although relations between rotation and exhumation in the Rhodope core complex have been postulated [Brun and Sokoutis, 2007;van Hinsbergen et al, 2008a], the region that could have experienced major extension-related rotations in the west lies offshore central or southwestern Greece (Figure 1).…”
Section: Hinsbergen Et Al: Exhumation With a Twistmentioning
confidence: 99%
“…5-8.5 kbar, 500-700°C) and associated migmatites also developed in the central Cyclades, such as in the Naxos, Paros, Mykonos and Ikaria islands [Jansen and Schuiling, 1976;Lister et al, 1984;Urai et al, 1990;Keay et al, 2001;Vanderhaeghe, 2004;Duchêne et al, 2006;Kruckenberg et al, 2011;Beaudoin et al, 2015;Laurent et al, 2015]. Exhumation of these rocks as MCCs was accommodated during the Oligocene-Miocene by several ductile-brittle detachment systems (figures 4 and 6) comprising the top-to-the NE North Cycladic Detachment System (NCDS) [Faure et al, 1991;Lee and Lister, 1992;Gautier and Brun, 1994;Mehl et al, 2005Mehl et al, , 2007Brichau et al, 2007Brichau et al, , 2008Jolivet et al, 2010a], the top-to-the N Naxos/Paros Extensional Fault System (NPEFS) [Urai et al, 1990;Gautier et al, 1993;Brichau et al, 2006;Seward et al, 2009;Bargnesi et al, 2013] and the top-to-the SW West Cycladic Detachment System (WCDS) [Grasemann and Petrakakis, 2007;Brichau et al, 2010;Iglseder et al, 2011;Grasemann et al, 2012]. The minimum offset of these extensional structures is estimated at 60-100 km for the NCDS [Jolivet et al, 2004a;Brichau et al, 2008] and ~50 km for the NPEFS (figure 3) [Brichau et al, 2006].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Further south, Oligocene-early Miocene exhumation of MCCs mainly in greenschist-facies conditions occurred in the Cyclades and the Menderes massif [Altherr et al, 1982;Lister et al, 1984;Gautier and Brun, 1994;Jolivet et al, 1994;Bozkurt and Oberhänsli, 2001;Vanderhaeghe and Teyssier, 2001;Ring et al, , 2010Catlos and Çemen, 2005;Jolivet & Brun, 2010], associated with additional HT-MP metamorphism affecting the northern Menderes massif and the central Cyclades in the Oligocene and early Miocene, respectively (figures 8n-r and 11) [Jansen and Schuiling, 1976;Lister et al, 1984;Gautier et al, 1993;Keay et al, 2001;Catlos and Çemen, 2005;Duchêne et al, 2006;Bozkurt et al, 2010;Beaudoin et al, 2015]. In the Cyclades, the NCDS accommodated this exhumation since the Oligocene (figures 9 and 11) [Faure et al, 1991;Lee and Lister, 1992;Brichau et al, 2007Brichau et al, , 2008Jolivet et al, 2010a] while the NPEFS and the WCDS became active in the early Miocene [Urai et al, 1990;Gautier et al, 1993;Vanderhaeghe, 2004;Brichau et al, 2006;Seward et al, 2009;Iglseder et al, 2011;Grasemann et al, 2012].…”
Section: Back-arc Extension In the Cyclades And Western Anatoliamentioning
confidence: 99%
See 2 more Smart Citations